The effect of cash flows from investment activities, size of firm and return on assets to stock price at indeks lq45 company on the indonesia stock exchange period 2014-2020 - Intan Zamarud; Kasmawati Kasmawati; Rani Munika; Syamsul Bahri (STIE Bangkinang Publishing, 2022)
This study aims to analyze the effect of cash flows from investment activities, size of firm and Return On Assets on stock price. The sample in this study were 19 LQ45 companies listed on the Indonesia Stock Exchange in 2014-2020. The sampling technique used was purposive sampling and obtained from the Indonesia Stock Exchange website (www.idx.co.id). The analytical technique used in this study is multiple linear regression. The results of the study indicate that size of firm has an influence on stock price. While the cash flows from investment activities and return on assets has no effect on stock price. The close relationship that occurs between the variables cash flows from investment activities, size of firm and return on assets is strong with a correlation coefficient of 58.6% while the contribution of independent variables to the related variables is 36.1% while 63.9% is explained by other variables not included in this study.